Intangible resources and internationalization for the innovation performance of Chinese high-tech firms - Yuhan Liu; Junic Kim; Jaewook Yoo (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
The purpose of this study is to explore the relationships between three intangible resources and the innovation performance of Chinese high-tech firms, and the moderating effect of internationalization on these relationships. We implement a hierarchical multiple regression analysis using data for 274 Chinese high-tech firms. The results show that all three intangible resources, measured by top management team diversity, research and development intensity, and government subsidies, positively influence Chinese high-tech firm innovation performance. We find the relationships between these intangible resources and the innovation performance of Chinese high-tech firms are significantly positively moderated by internationalization. These findings have important implications, as follows. First, they provide evidence of the strategic value of intangible resources and their effects on innovation performance. Second, our results show that increasing internationalization alone does not guarantee performance improvement. Firms should consider their internal and external environments and the complex relationships among factors when they make decisions about internationalization investments. Prior research does not provide an explanation for how internationalization affects performance, because it primarily focuses on the direct relationship between internationalization and performance. This study overcomes this limitation by examining the indirect effect of internationalization on performance.
Keywords: 650; Chinese high-tech companies; innovative performance; intangible resources; internationalization